A peculiar case of large primary cutaneous Ewing's sarcoma of the foot: Case report and review of the literature. (2015) - Grassetti, Luca; Torresetti, Matteo; Brancorsini, Donatella; Rubini, Corrado; Lazzeri, Davide; Di Benedetto, Giovanni
Highlights: Primary cutaneous Ewing sarcoma of the foot are rare and usually small tumors. The present case is the largest primary cutaneous Ewing sarcoma of the foot. We treated this tumor with surgery alone. These tumors should be considered into differential diagnosis of superficial lesions. Abstract: Introduction: Primary cutaneous extraskeletal Ewing's sarcomas (ESs) are extremely rare tumors, limited to the skin and generally appear as a single small lesion, circumscribed mid-to-deep dermis or involving subcutis. Due to their rarity and morphological similarity to other cutaneous tumors, ESs are subject to being clinically and pathologically subdiagnosed. Presentation of case: A 37-year-old man presented a large rapidly growing mass of the first toe measuring 9.5 × 8 cm with no radiological evidence of bone involvement. The patient underwent wide surgical tumor resection; histological, immunohistochemical and molecular evaluation confirmed the diagnosis of ESs. Postoperative examinations revealed no metastasis and after 11 months follow-up no recurrences were detected. Discussion: Current literature reports only a few isolated cases or small series. ESs are generally described as small masses with a favorable clinical behavior. Despite lower extremity is a relatively frequent site, only rare and small ESs of the foot have been reported. To our knowledge the present case is the largest ES of the foot. Despite its large size, the patient did not report any metastases confirming the hypothesis of treating superficial ES with surgery alone, thus avoiding adjuvant radiotherapy and/or chemotherapy and their related side-effects. Conclusion: ESs still remain exceedingly rare tumors and they could not be taken in consideration into differential diagnosis. This case represents a peculiar example of large ES in an uncommon site as the foot successfully treated with surgery alone, and may serve as an alert for those physicians who approach such rapidly growing superficial lesions.